1998
DOI: 10.1038/30741
|View full text |Cite|
|
Sign up to set email alerts
|

Acute stress facilitates long-lasting changes in cholinergic gene expression

Abstract: Acute traumatic stress may lead to post-traumatic stress disorder (PTSD), which is characterized by delayed neuropsychiatric symptoms including depression, irritability, and impaired cognitive performance. Curiously, inhibitors of the acetylcholine-hydrolysing enzyme acetylcholinesterase may induce psychopathologies that are reminiscent of PTSD. It is unknown how a single stressful event mediates long-term neuronal plasticity. Moreover, no mechanism has been proposed to explain the convergent neuropsychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
447
3
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 554 publications
(476 citation statements)
references
References 26 publications
21
447
3
5
Order By: Relevance
“…It is reported that when living brain slices from mice were exposed to AChE inhibitors such as physostigmine and pyridostigmine, AChE mRNA levels were markedly increased 30 min after treatment, followed by enhancement of AChE in cerebral cortical regions (Kaufer et al, 1998). By this reason, we have performed two baseline experiments, once (baseline-1) before and once (baseline-2) after the donepezil administration.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that when living brain slices from mice were exposed to AChE inhibitors such as physostigmine and pyridostigmine, AChE mRNA levels were markedly increased 30 min after treatment, followed by enhancement of AChE in cerebral cortical regions (Kaufer et al, 1998). By this reason, we have performed two baseline experiments, once (baseline-1) before and once (baseline-2) after the donepezil administration.…”
Section: Discussionmentioning
confidence: 99%
“…17 This may explain the therapeutic benefits of the antiglutamatergic agent memantine that has been observed in veterans with PTSD. Other studies also highlight the transient increase in the levels of acetyl choline and a phase of enhanced neuronal excitability following a period of stress, 18 possibly explaining the apparent exacerbation of PTSD symptoms in dementia patients who are taking acetylcholinesterase inhibitors. 19 Finally, with passage of time following trauma, PTSD patients also appear to show an increased fear response to a wide range of neutral cues, a phenomenon known as 'fear generalisation'.…”
Section: Biological Theoriesmentioning
confidence: 99%
“…30,40 Moreover it should also be mentioned that acetylcholinesterase inhibitors may induce psychopathologies reminiscent of posttraumatic stress disorders characterized by a series of neuropsychiatric symptoms including depression, 43 and also that stress has been shown to induce long lasting changes in cholinergic gene expression. 44 …”
Section: The Role Of Noradrenaline and Serotoninmentioning
confidence: 99%